PEMANFAATAN ENDAPAN LIMBAH CAIR PABRIK KELAPA SAWIT (ELCPKS) DAN KAPUR DOLOMIT PADA BIBIT KELAPA SAWIT(Elaeis guineensis Jacq.) DI MAIN NURSERY - Daniel Simangunsong; Wardati '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this research was to determine the influence of ELCPKS and dolomite interaction on oil palm seedling growth and get the best dose for oil palm seedling growth. This research was conducted at the experimental station of Agriculture Faculty, University of Riau on December 2013 until March 2014. This research was arranged on using Completely Randomized Design (CRD) with two factorial: Factor 1 ; dose of ELCPKS, L0 = Without ELCPKS, L1 = 25 g ELCPKS /polybag, L2 = 50 g ELCPKS of /polybag and L3 = 75 g ELCPKS of /polybag. Factor II ; dolomite D0 = Without dolomite/polybag, D1 = Giving 6 g dolomite /polybag, D2 =12 g dolomite /polybag, D3 = 18 g dolomite /polybag and repeated 3 times, so obtained 48 units experiment. Parameters observed were the increase of plant height, increase of stump diameter, increase of leaves number, root volume, root shoot ratio and dry weight. The result showed that ELCPKS and dolomite interaction affect on; increase of plant height, increase of stump diameter, root crown ratio and plant dry weight, but not significantly on increase of leaves number and root volume. The best results shows on 75 g ELCPKS of /polybag and 18 g dolomite /polybag. ELCPKS treatment on oil palm seedling affect to all parameters, meanwhile the dolomite lime treatment affect to all parameters except on increase of leaves number and root shoot ratio. Keywords : Oil palm seedling, ELCPKS, dolomite